Comparison Analysis of Conventional Economic Systems and Islamic Economy on Demand Concept - Meriyati Meriyati; M Nasyah Agus Saputra; Sarah Lutfiyah Nugraha (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri, 2022)
Economic activity will not be separated from the existence of a demand such as buying and selling. The number of requests from buyers / consumers will affect the price of an item sold. The theory of demand will also not be separated from microeconomics. Humans often make purchase transactions based on mere desire so that the demand for an item becomes high. Meanwhile, based on Islamic economic theory based on the Qur'an and Hadith as well as the ijtihad of the scholars, the demand for an item or purchase is not based on mere desire, but is prioritized on things needed by humans.